Dental erosion treatment with stainless steel crowns: case report - Muñoz - Villanueva, Magali (2020)
Dental erosion is the chronic and painless loss of the hard tissue of the tooth produced by acidic or chelating agents without bacterial involvement. The aim of this case report is to describe the comprehensive oral rehabilitation of a patient with dental erosion due to gastric reflux. This report describes the case of a patient that shows dental caries on occlusal surfaces of pieces 55 and 65 and wear on occlusal surfaces with compromise of dentin in pieces 64, 74, 75, 84 and 85. The decayed pieces were restored with composite resin and the pieces with occlusal wear were restored with stainless steel crowns. Post treatment follow ups were performed.  The integral rehabilitation had a positive impact on the patient since the development of the masticatory and aesthetic functions were improved.